Prevalence of hard ticks (acari: ixodidae) in spur-thighed tortoise (testudo graeca ibera) population of konya - Uğur Uslu; Muhammad Sohail Sajid; Onur Ceylan; Adil Ejaz (Eurasian Journal of Veterinary Sciences)
Aim:This study was carried out to determine the prevalence of ixodid tick species which play a role in the transmission of many diseases in humans and animals in spur-thighed tortoises. Materials and Methods: Ticks were brought to the Laboratory of Parasitology by putting in sample collection bottles containing 70% ethanol and and were taxonomically identified was using standard keys. Results: All tortoises were found infested with ticks. Three species of ticks viz; Hyalomma aegyptium, H. marginatum marginatum and Rhipicephalus turanicus were detected in the tortoises. Majority of tortoises (89.2%) were found infested with H. aegyptium only. However, seven (10.8%) were found infested with more than one tick species (4 of 7 co-infested with H. aegyptium and R. turanicus and 3 of 7 co-infested with H. aegyptium and H. m. marginatum). Earlier, H. aegyptium was the only tick species reported from tortoises of Turkey. As a result of this study, H. m. marginatum and R. turanicus have also been shown to be infestation agents. Conclusion: It is concluded that the contiguous population of tortoises in Konya region together with optimum environmental compatibility favor the settlement and propagation of hard ticks in the tortoise population.